2018
DOI: 10.1155/2018/6945743
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics, Prognosis, and Risk Factors of Lymph Node Metastasis in Early Gastric Cancer

Abstract: Background Lymph node metastasis (LNM) is the most important risk factor for endoscopic treatment in early gastric cancer (EGC) patients. We aimed to investigate the rate of LNM, the risk factors, and the prognosis of EGC patients with LMN. Methods A total of 10,039 patients who underwent gastrectomy with lymphadenectomy were reviewed between January 2010 and December 2015 at Jiangsu Province Hospital in China. Among them, we identified 1004 (10%) EGCs. First, endoscopic and clinicopathological features relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
4
24
1
4
Order By: Relevance
“…In the present study, the infiltration depth, gross type and intravascular cancer embolus were independent risk factors for lymph node metastasis in patients with Siewert II/III AEG. Previous studies have reported that the LNM rate was significantly increased following an increase in the tumor infiltration [30]. The present study indicated similar outcomes demonstrating that the LNM rate was increased from 0 to 88.1% when the tumor infiltrated deeper gradually.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the infiltration depth, gross type and intravascular cancer embolus were independent risk factors for lymph node metastasis in patients with Siewert II/III AEG. Previous studies have reported that the LNM rate was significantly increased following an increase in the tumor infiltration [30]. The present study indicated similar outcomes demonstrating that the LNM rate was increased from 0 to 88.1% when the tumor infiltrated deeper gradually.…”
Section: Discussionsupporting
confidence: 88%
“…demonstrated that tumor size, histological type, presence of ulcerative finding and presence of lymphovascular involvement were independent risk factors of LNM (19). Other studies also revealed that overexpression of CD44v6, increased tumor markers [carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9, CA125], gender, age at diagnosis were also associated with LNM (20-23). However, most of these risk factors mentioned above were postoperative findings which were not available before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have previously concluded that the overall 3-year survival rate was higher in patients without LNM and that patients with LNM had a higher rate of tumor recurrence[25]. Several factors are associated with an increased rate of LNM.…”
Section: Discussionmentioning
confidence: 99%